Variability of C‐reactive protein in first‐generation Ecuadorian immigrants living in the United States. Issue 6 (1st December 2020) - Shattuck‐Heidorn, Heather; Eick, Geeta N.; Kramer, Karen L.; Sugiyama, Lawrence S.; Snodgrass, James Josh; Ellison, Peter T.
Abstract: Objectives: Establish the variability of C‐reactive protein (CRP) within a population of first‐generation immigrants living in the United States. Prior work has theorized that individuals with high levels of childhood pathogen exposure may have lower CRP levels in adulthood, and therefore that for these individuals, CRP may not be as accurate an index of chronic disease risk related to low‐level inflammation as is presumed based on data from wealthy populations. This potentially has major implications for the interpretation of CRP as a biomarker of chronic inflammation. Methods: This longitudinal study collected a total of 125 dried blood spot (DBS) samples from 31 participants (median 4 samples each) and CRP levels in these DBS were assayed by enzyme‐linked immunosorbant assay. Surveys were administered to characterize childhood pathogen exposure, and current illness. Variance was estimated using mixed effects regression models. Results: On average, participants were adults (mean = 41.9 years old) who had immigrated to the United States nearly 20 years prior to the study and had nearly universally experienced childhood helminth infection and other major pathogen exposures. Median serum‐equivalent CRP was 0.77 mg/L. Individuals reliably differed in subacute CRP levels, and, depending on whether untransformed or log‐transformed CRP was the outcome variable, 45% or 62% of variance in CRP was attributable to between‐individual differences. Conclusions: The variability of CRP levels in individuals with relatively high childhood pathogen exposure is comparable to previously reported studies in North America and Europe. However, CRP values are relatively low. CRP is an appropriate measure of subacute inflammation in this sample.